Characterization, antioxidant activity, and mineral profiling of Auricularia cornea mushroom strains - Khan, Asif Ali; Lu, Li-Xin; Yao, Fang-Jie; Fang, Ming; Wang, Peng; Zhang, You-Min; Meng, Jing-Jing; Ma, Xiao-Xu; He, Qi; Shao, Kai-Sheng; Wei, Yun-hui; Xu, Baojun (Frontiers in Nutrition, 2023)
Background: Edible mushrooms are healthy food rich in nutrients and active ingredients, the current mushroom breeding targets focused on high yield and superior quality, However, no previous breeding studies have been conducted in improving nutritional and health benefits of mushroom Auricularia cornea. Materials and Methods: The time required for fruiting body formation and bio efficiency of a total of 50 strains of A. cornea were studied through cultivation experiments. The antioxidant activity was evaluated via colorimetric methods. The crude polysaccharides and mineral contents were quantified analyzed. Results: The results showed that the time required for fruiting body formation and biological efficiency varied significantly among the strains. The wild domesticated strain Ac13 of A. cornea mushroom showed the shortest fruit development time (80 days). Hybrid strains Ac3 and Ac15 possessed the highest yield and biological efficiency. Hybrid strains Ac18 and cultivated strains Ac33 showed the highest content of crude polysaccharides, while cultivated strains Ac1 and Ac33, had the highest content of total polysaccharides in the fruiting body. In the case of mineral content, the highest zinc contents were observed from the cultivated strain Ac46 (486.33 mg·kg-1). The maximum iron content was detected from the hybrid strain Ac3 (788 mg·kg-1) and the wild domesticated strain Ac28 (350 mg·kg-1). The crude polysaccharides of the A. cornea strain showed significant antioxidant potential, and the ability of Ac33 and Ac24 to scavenge DPPH radicals and ABTS was significantly improved compared to other strains, respectively. The differences and similarities between the agronomic traits and chemical compounds of A. cornea mushroom strains were subjected to principal component analysis, which presented that cultivated, wild domesticated and hybrid strains of A. cornea possessed varied characteristics based on growth, yield and nutritional aspects. Conclusion: The crude polysaccharides from A. cornea mushroom strains act as natural antioxidants, the wild, hybrid, and commercial A. cornea mushroom strains can achieve rapid growth, early maturation, and high yields. The evaluation of biochemical indexes and nutritional characteristics of strains with excellent traits provided a scientific basis for initiating high-quality breeding, provided germplasm resources for the production of "functional food" with real nutritional and health value.